2016
DOI: 10.1039/c6cs00116e
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide-directed synthesis of luminescent self-assembly supramolecular structures and mechanically bonded systems from acyclic coordinating organic ligands

Abstract: Herein some examples of the use of lanthanide ions (f-metal ions) to direct the synthesis of luminescent self-assembly systems (architectures) will be discussed. This area of lanthanide supramolecular chemistry is fast growing, thanks to the unique physical (magnetic and luminescent) and coordination properties of the lanthanides, which are often transferred to the resulting supermolecule. The emphasis herein will be on systems that are luminescent, and hence, generated by using either visibly emitting ions (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
113
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 234 publications
(114 citation statements)
references
References 228 publications
0
113
0
1
Order By: Relevance
“…[1,2] Besides their widespreada pplicationsi nt he solid state, [3,4] lanthanide complexes also show great potentiala pplication in bulk solutions. [5,6] In general, the f-f transition of lanthanide(III) ions is Laporte-forbidden, and organic molecules that can coordinate or chelate with the lanthanide(III) ions (i.e., ligands) are neededt oa ctivate the energy transfer. [7,8] b-Dicarbonyl compounds with two adjacent Oa toms for coordination have been frequently used as ligands for lanthanide(III) ions, which are superior to monodentate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Besides their widespreada pplicationsi nt he solid state, [3,4] lanthanide complexes also show great potentiala pplication in bulk solutions. [5,6] In general, the f-f transition of lanthanide(III) ions is Laporte-forbidden, and organic molecules that can coordinate or chelate with the lanthanide(III) ions (i.e., ligands) are neededt oa ctivate the energy transfer. [7,8] b-Dicarbonyl compounds with two adjacent Oa toms for coordination have been frequently used as ligands for lanthanide(III) ions, which are superior to monodentate ligands.…”
Section: Introductionmentioning
confidence: 99%
“…16 More recently, Mercuri et al reported 2D-nanosheets of layered CPs using near-infrared-emitting lanthanide ions. 14 2,2':6 0 ,2 00 -terpyridine based ligands have been utilized successfully as antenna groups for lanthanide sensitization, 19,20,48,49 as well as for their spontaneity to form coordination bonds with Ln(III) ions. The terpyridine moiety acted as an antenna by absorbing electromagnetic radiation upon irradiation and transferring this energy to the excited state 5 D 0 of Eu(III) and 5 D 4 of Tb(III) through energy transfer from the triplet excited state (T 1 ) of the terpyridine by intersystem crossing (ISC) and subsequent deactivation (luminescence) to the 7 F J ground states.…”
Section: Introductionmentioning
confidence: 99%
“…The terpyridine moiety acted as an antenna by absorbing electromagnetic radiation upon irradiation and transferring this energy to the excited state 5 D 0 of Eu(III) and 5 D 4 of Tb(III) through energy transfer from the triplet excited state (T 1 ) of the terpyridine by intersystem crossing (ISC) and subsequent deactivation (luminescence) to the 7 F J ground states. 19,20,48,49 Furthermore, appropriate terpyridine derivatives have also been exploited to prepare coordination nanosheets. 10,11,21 With the recent surge in the illegitimate use of certain explosives by various organized agencies, there is an urgent need for effective recognition and quantication of such explosives for efficient security screening, homeland security, and environmental protection.…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 1) Crystals 2017, 7, 199 2 of 10 d 10 transition metal ions (Zn and Cd) and π-conjugated ligands, whereas coordination polymer materials based on lanthanide ions have been rarely published [24]. The advantages of those lanthanide materials over the transition metal luminescent materials include the sharp and strong emissions, large stokes shifts, high quantum yields, and long luminescence lifetimes, which originate from f-f transitions of lanthanide ions [25]. Taking into account these kinds of sensor materials are still defective, the synthesis and development of new materials based on lanthanide CPs for fluorescent high selective detection of acetones is still a major challenge.…”
Section: Crystal Structuresmentioning
confidence: 99%